Quantum clocks and the temporal localisability of events in the presence of gravitating quantum systems - Esteban Castro-Ruiz (Nature Portfolio, 2020)
Analysing the space-time metric of quantum phenomena is complicated by the absence of a consistent theory of quantum gravity. Here, the authors show how to describe the space-time metric for multiple observers who are keeping time with quantum clocks, which interact gravitationally with each other.